Exploring the Criticality and Impact of DevOps Practices - ARVEDAHL, MARTIN; ÅKERSTEN, CHRISTOPHER (My University, 2018)
The purpose of the study has been to explore DevOps practices with regards to their criticality on DevOps adoption goals, making grounds for decision making in the industry and for further research. Through performing a qualitative multiple case study on practitioners of DevOps, with existing literature as input, a set of adoption goals, practices and effects was elicited. The multiple case study consisted of interviewing and surveying twelve practitioners of DevOps in various software organizations, with different levels of experience. We have found that there seems to be a set of practices shared among practitioners, such as Automatic Testing & System Monitoring, critical for a set of shared adoption goals like Throughput. Some of these practices are transforming the way of working in the industry with regards to organizing operations. We further found that the implementation of the practices seems to have a significant effect on considered adoption goals, motivating further research. Lastly, we found that practitioners in the industry are not operationalizing DevOps, often not measuring the effects of adoption. However, some suggested metrics for verifying the effect of implementing DevOps practices have been found.
Keywords: DevOps; Goals; Practices; Effects